The Influence of Job Insecurity and Job Satisfaction on Organizational Commitment of Female Contract Operators in the Weaving Department of PT X, Cimahi City - Jasmine Alya Zahra; Juddy Prabowo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Direct labor plays an important role in the smooth production process. Textile manufacturing companies located in Cimahi City require skilled human resources to carry out their work. Organizational commitment is an important element in human resource management to achieve organizational goals. Factors that influence organizational commitment are job insecurity and job satisfaction. This study aims to determine the effect of job insecurity and job satisfaction on organizational commitment in female contract operators of the Weaving Department of PT X, both partially and simultaneously. This study uses a quantitative method with multiple regression analysis using SPSS version 27. Data collection methods used in this study are questionnaires and interviews. Respondents in this study were 79 female contract operators of the Weaving Department of PT X. The results of the study indicate that job insecurity does not affect organizational commitment and job satisfaction has a positive effect on organizational commitment. Then, job insecurity and job satisfaction simultaneously have a significant effect on organizational commitment.